Substorms and polar cap convection: the 10 January 2004 interplanetary CME case - Y. Andalsvik; P. E. Sandholt; C. J. Farrugia (Annales Geophysicae, 2012)
The expansion-contraction model of Dungey cell plasma convection has two different convection sources, i.e. reconnections at the magnetopause and in the magnetotail. The spatial-temporal structure of the nightside source is not yet well understood. In this study we shall identify temporal variations in the winter polar cap convection structure during substorm activity under steady interplanetary conditions. Substorm activity (electrojets and particle precipitations) is monitored by excellent ground-satellite DMSP F15 conjunctions in the dusk-premidnight sector. We take advantage of the wide latitudinal coverage of the IMAGE chain of ground magnetometers in Svalbard – Scandinavia – Russia for the purpose of monitoring magnetic deflections associated with polar cap convection and substorm electrojets. These are augmented by direct observations of polar cap convection derived from SuperDARN radars and cross-track ion drift observations during traversals of polar cap along the dusk-dawn meridian by spacecraft DMSP F13. The interval we study is characterized by moderate, stable forcing of the magnetosphere-ionosphere system ( E KL = 4.0–4.5 mV m −1 cross polar cap potential (CPCP), Φ (Boyle) = 115 kV) during Earth passage of an interplanetary CME (ICME), choosing an 4-h interval where the magnetic field pointed continuously south-west ( B z < 0; B y < 0). The combination of continuous monitoring of ground magnetic deflections and the F13 cross-track ion drift observations in the polar cap allows us to infer the temporal CPCP structure on time scales less than the ~10 min duration of F13 polar cap transits. We arrived at the following estimates of the dayside and nightside contributions to the CPCP (CPCP = CPCP/day + CPCP/night) under two intervals of substorm activity: CPCP/day ~110 kV; CPCP/night ~50 kV (45% CPCP increase during substorms). The temporal CPCP structure during one of the substorm cases resulted in a dawn-dusk convection asymmetry measured by DMSP F13 which is opposite to that expected from the ...